2011
DOI: 10.1111/j.1365-313x.2011.04821.x
|View full text |Cite
|
Sign up to set email alerts
|

An ABA‐regulated and Golgi‐localized protein phosphatase controls water loss during leaf senescence in Arabidopsis

Abstract: SUMMARYIt is known that a senescing leaf loses water faster than a non-senescing leaf and that ABA has an important role in promoting leaf senescence. However, questions such as why water loss is faster, how water loss is regulated, and how ABA functions in leaf senescence are not well understood. Here we report on the identification and functional analysis of a leaf senescence associated gene called SAG113. The RNA blot and GUS reporter analyses all show that SAG113 is expressed in senescing leaves and is ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
145
1
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(151 citation statements)
references
References 54 publications
4
145
1
1
Order By: Relevance
“…However, our work provides the first indication of the post-transcriptional regulation of PP2C expression and phosphatase activity in ABA signalling and plant responses to ABA. Previously, it was shown that the nine PP2Cs differ in their subcellular localization 11,29,34 and interactions with PYLs 5,12,13,29 . Our findings suggest that the regulatory mechanisms of PP2Cs are more complex than previously thought, and the post-transcriptional regulation of PP2C expression adds another layer of complexity to ABA signalling and plant adaptation to stress.…”
Section: Discussionmentioning
confidence: 99%
“…However, our work provides the first indication of the post-transcriptional regulation of PP2C expression and phosphatase activity in ABA signalling and plant responses to ABA. Previously, it was shown that the nine PP2Cs differ in their subcellular localization 11,29,34 and interactions with PYLs 5,12,13,29 . Our findings suggest that the regulatory mechanisms of PP2Cs are more complex than previously thought, and the post-transcriptional regulation of PP2C expression adds another layer of complexity to ABA signalling and plant adaptation to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, RPK1 is an upstream component of ABA signaling and its expression is increased in an ABA-dependent manner throughout the progression of leaf senescence. However, induction of RPK1 expression in young plants leads to retarded growth but does not trigger the senescence symptoms, suggesting that function of RPK1 in ABAinduced leaf senescence is dependent on the developmental age.Senescence-associated gene113 (SAG113) is a negative regulator of ABA signaling controlling water loss during senescence in Arabidopsis [5]. SAG113 encodes a Golgi-localized PP2C family protein phosphatase, which is able to complement the yeast PP2C-deficient ptd1 mutant, confirming that SAG113 is the functional ortholog of PTC1.…”
mentioning
confidence: 93%
“…1 Our current work has shown that stomatal opening was enhanced with prolonged MeJA treatment and vacuolar lumen was alkalized. The enhanced stomatal aperture was also found in low-acidified vacuolar lumen in MeJA-induced leaf senescence.…”
mentioning
confidence: 97%
“…1 As we know, water control is mostly dependent on stomatal movement. Recent report has reported that vacuolar acidification has a key role in ABAinduced stomatal closure.…”
mentioning
confidence: 99%